An Altered Splicing Registry Explains the Differential ExSpeU1-Mediated Rescue of Splicing Mutations Causing Haemophilia A - Balestra, Dario; Maestri, Iva; Branchini, Alessio; Ferrarese, Mattia; Bernardi, Francesco; Pinotti, Mirko (Frontiers in Genetics, 2019)
The exon recognition and removal of introns (splicing) from pre-mRNA is a crucial step in the gene expression flow. The process is very complex and therefore susceptible to derangements. Not surprisingly, a significant and still underestimated proportion of disease-causing mutations affects splicing, with those occurring at the 5’ splice site (5’ss) being the most severe ones. This led to the development of a correction approach based on variants of the spliceosomal U1snRNA, which has been proven on splicing mutations in several cellular and mouse models of human disease. Since the alternative splicing mechanisms are strictly related to the sequence context of the exon, we challenged the U1snRNA-mediated strategy in the singular model of the exon 5 of coagulation factor (F)VIII gene (F8) in which the authentic 5’ss is surrounded by various cryptic 5’ss. This scenario is further complicated in the presence of nucleotide changes associated with FVIII deficiency (Haemophilia A), which weaken the authentic 5’ss and create/strengthen cryptic 5’ss. We focused on the splicing mutations (c.602-32A>G, c.602-10T>G, c.602G>A, c.655G>A, c.667G>A, c.669A>G, c.669A>T, c.670G>T, c.670+1G>T, c.670+1G>A, c.670+2T>G, c.670+5G>A and c.670+6T>C) found in patients with severe to mild Haemophilia A. Minigenes expression studies demonstrated that all mutations occurring within the 5’ss, both intronic or exonic, lead to aberrant transcripts arising from the usage of two cryptic intronic 5’ss at positions c.670+64 and c.670+176. For most of them, the observed proportion of correct transcripts is in accordance with the coagulation phenotype of patients. In co-transfection experiments, we identified a U1snRNA variant targeting an intronic region downstream of the defective exon (Exon Specific U1snRNA, U1sh7) capable to re-direct usage of the proper 5’ss ( 80%) for several mutations. However, deep investigation of rescued transcripts from +1 and +2 variants revealed only the usage of adjacent cryptic 5’ss, leading to frameshifted transcript forms. These data demonstrate that a single ExSpeU1 can efficiently rescue different mutations in the F8 exon 5, and provide the first evidence of the applicability of the U1snRNA-based approach to Haemophilia A.